An Element of Practical Knowledge in Education: Professional routines - Lacourse, France (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2011)
The question of practical knowledge and its teaching has arisen more perceptibly since the appearance of the aim to professionalize teachers. How can imperceptible knowledge such as professional routines be taught? To establish a social fabric and effective class management, it is essential to call on creative and adaptive professional routines. These routines support the interpretation of daily life, effectiveness, and a sense of security among both students and teachers; it is a frame favouring successful classroom management. Professional routines come under the scope of integrated competencies, and this prompts their analysis in view of understanding a central link within initial training. This paper will present the concept of professional routines as an educational practice in which practical knowledge is combined with professional learning, then the conceptual frame, the analytical method, and the results of two research projects, followed by a concluding reflection.